Empowerment group therapy for refugees with affective disorders: results of a multicenter randomized controlled trial - Maren Wiechers; Michael Strupf; Malek Bajbouj; Kerem Böge; Carine Karnouk; Stephan Goerigk; Inge Kamp-Becker; Tobias Banaschewski; Michael Rapp; Alkomiet Hasan; Peter Falkai; Andrea Jobst-Heel; et al. (European Psychiatry, 2023)
Abstract